What We Talk about When We Talk about Rigor: Examining Conceptions of Academic Rigor. (10th November 2021) - Culver, K. C.; Braxton, John M.; Pascarella, Ernest T.
ABSTRACT: Academic rigor has long been considered important for students' learning and development in higher education. However, findings about students' outcomes from previous studies of rigor are mixed, in part because of varying conceptions of what constitutes rigor. In quantitative research, rigor is often operationalized in one of two ways: through students' workload in courses or through their instructors' expectations for course learning in the form of cognitive challenge. This study employed data from a multi-institutional, longitudinal study of undergraduates in the United States to examine the relationship of both conceptions of rigor with students' cognitive development, including their critical thinking skills and two measures of self-motivated learning (need for cognition and positive attitudes toward literacy). Workload was related to four-year growth in positive attitudes about reading and writing, while cognitive challenge was related to self-motivated learning in year one and all three aspects of cognitive development in year four. In particular, the amount of reading that students completed was the only measure of workload positively associated with outcomes, while both challenge in class and in exams and assignments played a role. These findings have implications for instructors, instructional developers, institutional leaders, and researchers in higher education.